Isolated displaced fracture of humeral trochlea: a report of two rare cases - Kwan, M.K.; Khoo, E.H.; Chua, Y.P.; Mansor, A. (2007)
Fracture of thehumeral trochlea is usually associated with elbow dislocations or capitellar fracture.3-5 Isolated trochlea fracture in adult is a surgical rarity as compared to its capitellar counterpart.5 This fracture is not mentioned in the standard orthopaedic textbook. It only appears sporadically in literature as a case report.2,6,8 The rarity of this fracture is probably a result of its anatomical location which is sited deep within the olecranon fossa. Therefore, there is still very little known regarding the mechanism of injury and the treatment results of this injury. Isolated fracture of the humeral trochlea was first described by Laugier in 1853 and later credited by Stimson. Thus, the trochlea fracture is also sometimes known as Laugier's fracture.7 We would like to report two cases of isolated displaced trochlea fracture that were treated with open reduction and internal fixation using the standard (non-cannulated) Herbert screw (Zimmer, Warsaw, Indiana).